Increasing access without compromising quality: optimizing telemedicine care in pediatric rheumatology - Jones, S.; Toth, M.; Liu, A. B.; Morgan, E. M.; Leal, J.; Goh, Y. I.; Hayward, K. (Frontiers in Pediatrics, 2025)
Juvenile idiopathic arthritis (JIA) is a chronic immune-mediated condition affecting approximately 1 in 1,000 children in the United States. Without appropriate treatment, JIA can lead to permanent disability, chronic pain, and impaired quality of life. Targeted treatment strategies have enabled some patients to achieve sustained inactive disease and improved outcomes. However, the ongoing workforce shortage of pediatric rheumatologists poses a barrier to accessing effective care for many patients and families. Telemedicine is a potential solution to improving access to care for patients who travel significant distances to obtain pediatric rheumatology healthcare. During the COVID-19 pandemic, telemedicine saw rapid adoption with exponential uptake in use during unprecedented circumstances and resulted in inconsistent implementation of this emerging healthcare modality. While virtual visits offer many benefits, they often fail in gathering critical data elements required for measuring and tracking health outcomes, engaging in data-driven shared decision making, population health management and secondary research. In response to these challenges, the Pediatric Rheumatology Care and Outcomes Improvement Network (PR-COIN) Digital Health Workgroup conducted a needs assessment among its members to identify opportunities and barriers for optimizing telemedicine visits for patients with JIA. Based on this assessment, potential interventions and instructional materials were developed and compiled into a “change package” to assist rheumatology teams in planning, implementing and evaluating improvements to telemedicine visits at their centers. This change package is publicly available on the PR-COIN website for adoption and use (https://www.pr-coin.org/center-tools-resources). Continuous evaluation and adaptation of these tools are essential as telemedicine practices continue to evolve.